Pengembangan LKPD Terintegrasi STEM-PjBL (Science, Technology, Engineering, And Mathematics-Project Based Learning) pada Materi Termokimia - Suci Sukmawati Syafe'i; Effendi Effendi (Edukimia, 2020)
This research produce LKPD STEM-PjBL (Science, Technology, Engineering, and Mathematics-Project Based Learning) integrated on Thermochemical learning, then reveal its validity and practicality categories. This type of research is Research and Development, with 4-D model consisting of: (1) define, (2) design, (3) develop, and (4) disseminate. LKPD was validated by 3 Chemistry lecturers of FMIPA UNP and 2 Chemistry teachers, then practicalited by 2 Chemistry teachers and 25 students of Class XII MIA 2 SMA UNP Laboratory Development. The validity and practicality tests were using Cohen kappa analysed, yielding 0.816 for the validity test and 0.837 and 0.855 for the teacher and student practicality test with very high categories. The data shows that the LKPD produced is valid and practical.